Study of thermostable chitinase isolated and purified from Oryctes rhinoceros larvae gut - Aisyah Nabila Idris,; Tang, Swee Seong; Ahmad Faris Mohd Adnan, (Penerbit Universiti Kebangsaan Malaysia, 2021)
A chitinase-producing bacteria was locally isolated from rhinoceros beetle (Oryctes rhinoceros) larvae gut discovered in mushroom compost. A strain was selected from the source and labeled as RBLG1. It was identified using 16s rDNA sequencing and has strong homology to Bacillus cereus. Chitinase produced from RBLG1 was purified using ammonium sulfate precipitation, ion exchange chromatography, and gel filtration. The purified chitinase from RBLG1 shows the homogeneity 1.9 fold after the gel filtration process. The purified chitinase was identified and analyzed using SDS-PAGE and the molecular mass from the strain was approximately 40 kDa. Further assays were performed to study the effect of temperature, pH, and metal ion on the purified enzyme. The purified enzyme shows highest chitinase activity at pH 4 and 60 °C. For metal ion test, chitinase from RBLG1 was unaffected when treated by various ions. Kinetic performance of chitinase using Michaelis-Menten equation shows Km and Vmax values were 2.3 mM and 0.0294 [P] mM/min, respectively.